MKK4-MPK3-WRKY17-mediated salicylic acid degradation increases susceptibility to Glomerella leaf spot in apple - Shan, Dongqian (Plant Physiol, 2021)
Glomerella leaf spot (GLS), a fungal disease caused by Colletotrichum fructicola, severely affects apple quality and yield, yet few resistance genes have been identified in apple (Malus domestica Borkh.). Here we found a transcription factor MdWRKY17 significantly induced by C. fructicola infection in the susceptible apple cultivar “Gala.” MdWRKY17 overexpressing transgenic “Gala” plants exhibited increased susceptibility to C. fructicola, whereas MdWRKY17 RNA-interference plants showed opposite phenotypes, indicating MdWRKY17 acts as a plant susceptibility factor during C. fructicola infection. Furthermore, MdWRKY17 directly bound to the promoter of the salicylic acid (SA) degradation gene Downy Mildew Resistant 6 (MdDMR6) and promoted its expression, resulting in reduced resistance to C. fructicola. Additionally, Mitogen-activated protein kinase (MAPK) 3 (MdMPK3) directly interacted with and phosphorylated MdWRKY17. Importantly, predicted phosphorylation residues in MdWRKY17 by MAPK kinase 4 (MdMEK4)-MdMPK3 were critical for the activity of MdWRKY17 to regulate MdDMR6 expression. In the six susceptible germplasms, MdWRKY17 levels were significantly higher than the six tolerant germplasms after infection, which corresponded with lower SA content, confirming the critical role of MdWRKY17-mediated SA degradation in GLS tolerance. Our study reveals a rapid regulatory mechanism of MdWRKY17, which is essential for SA degradation and GLS susceptibility, paving the way to generate GLS resistant apple.